Pengaruh Posisi Miring Menggunakan Peanut Ball terhadap Lama Kala I Fase Aktif pada Ibu Bersalin: The Effect of Inclined Position Using Peanut Ball on the Duration of the Active Phase I in Maternal Mothers - Shadrina, Yasmin Alya; Asiyah, Nor; Khoirunnisa’, Fania Nurul (Chakra Brahmanda Lentera Institute, 2026)
Normal delivery is a physiological process that ends with the birth of the fetus and placenta. However, the extension of the active phase still often occurs and has the potential to cause complications such as bleeding, infection, and maternal fatigue. Safe and simple nonpharmacological measures are needed to accelerate labor. A primary therapeutic method available involves the left-tilt position with a peanut ball, which expands the pelvic cavity, optimizes contraction efficiency, and accelerates fetal vertex progression. This inquiry employs a numerical analytical framework using a quasi-experimental post-test-only control-group methodology. The participants were 45 healthy mothers in labor recruited through a deliberate selection procedure. The intervention group was given a left-leaning position using a peanut ball, while the control group was without a tool. Information acquisition was executed through monitoring using a partograph and a chronometer to quantify the length of the first phase of the active phase. Evidence examination used an independent t-test or a Mann-Whitney test at the significance threshold of α = 0.05. The findings revealed that the mean length of the first stage of the active phase in the treatment cohort was shorter than that of the comparison group. Numerical assessments indicate that a substantial disparity exists between the two clusters (p < 0.05), suggesting that the use of peanut balls in the left-leaning position is effective in accelerating the progress of labor during the I phase. The left-slanted position with the peanut ball has been shown to provide physiological benefits by optimizing uteroplacental circulation, increasing contraction strength, and promoting pelvic dilation. This intervention can be an innovative, safe, and easy-to-apply alternative in obstetric practice to speed up labor, improve maternal comfort, and support evidence-based labor services.